STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAK SISWA MELALUI BUDAYA RELIGIUS SEKOLAH DI SMP NEGERI 2 GEMOLONG SRAGEN - Mohammad Said Saifudin; Laila Hidayatul Amin; Faruq Alhasbi (Jurnal Manajemen Pendidikan, 2026)
This study analyzed Islamic Religious Education teachers’ strategies for developing the moral character of ninth-grade students at SMP Negeri 2 Gemolong Sragen and identified supporting and inhibiting factors. It used a descriptive qualitative approach and field research design. Informants included Islamic Religious Education teachers across three grade levels, along with student representatives. Data were collected through observation, semi-structured interviews, and documentation. Credibility was established through source and technique triangulation, while analysis involved data condensation, data display, conclusion drawing, and verification. The findings revealed three strategies: enforcing discipline, providing teacher role models, and habituating religious practices. These strategies were implemented through morning Qur’anic recitation, Duha prayer, congregational Zuhr prayer, Friday charity, school regulations, and the 5S culture. Supporting factors included religious programs, school culture, collaboration, and worship facilities. Inhibiting factors included limited parental involvement, peer influence, social media exposure, and supervision outside school. The findings emphasize integrated management involving Islamic Religious Education, role modelling, habituation, school culture, supervision, and family partnerships.